Quality of life assessment in ocular toxoplasmosis in a Colombian Population (2011)
The participants were 29 otherwise healthy patients with retinochoroidal lesions consistent with Toxoplasma infection. The controls were 29 gender and age-matched people with normal visual function who came from the same socioeconomic and educational background as the participants. The authors used the version of the National Eye Institute 25-item visual function questionnaire (NEI VFQ25).